Transmission of Grapevine Leafroll-associated Virus 3 by Vine Mealybug, Planococcus ficus (Signoret), to Grapevines Treated with Imidacloprid - Allsopp, E. (South African Journal of Enology and Viticulture, 2016)
Grapevine leafroll disease is widely accepted to be the most damaging grapevine virus disease in South Africa. The current industry strategy to limit leafroll infection in new vineyards includes treating newly planted grapevines with a systemic insecticide like imidacloprid and rogueing all grapevines that exhibit leafroll symptoms. A tendency by some producers to eschew rogueing and rely solely on imidacloprid applications to control vine mealybug and so protect new vineyards from leafroll infection gave rise to this study. Two bioassays were conducted to determine if Planococcus ficus (Signoret) nymphs can transmit grapevine leafroll-associated virus 3 (GLRaV-3) to potted indicator grapevines treated with imidacloprid applied through the soil five months before exposure to viruliferous mealybugs. Ten of 21 leafroll-free grapevines treated with imidacloprid tested positive for GLRaV-3 seven to eight weeks after being exposed to viruliferous first- and second-instar P. ficus nymphs. This means that the systemic applications of imidacloprid to newly planted, virus-free vineyards will not necessarily protect the vines from GLRaV-3 if they become infested by viruliferous vine mealybugs, although the insecticide provides effective mealybug control and helps to prevent the secondary spread of leafroll infection in these vineyards. To control the spread of leafroll virus to newly planted, leafroll-free vineyards, all grapevines that serve as sources of infection should be removed. Where this is not feasible, vectors should be monitored and controlled rigorously in infested and disease-free vineyards alike, while all infected grapevines should be removed from new vineyards as they begin to develop leafroll symptoms.